Reversing climate progress: consequences and solutions in the wake of U.S. policy rollbacks - Carlos Garcia-Soto (npj Climate Action)
U.S. climate policy rollbacks under President Trump threaten to reverse international climate progress but also may catalyze renewed global urgency. The environmental, economic, and geopolitical consequences of these policies are examined, and five strategic responses are proposed—from new international climate alliances to accelerating renewable energy development and empowering subnational efforts. The article urges a global response to maintain momentum toward the Paris Agreement goals amid increasing challenges.